2004
DOI: 10.1111/j.0962-1075.2004.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

The dMRP/CG6214 gene of Drosophila is evolutionarily and functionally related to the human multidrug resistance‐associated protein family

Abstract: ATP-binding cassette (ABC) transporters are involved in the transport of substrates across biological membranes and are essential for many cellular processes. Of the fifty-six Drosophila ABC transporter genes only white, brown, scarlet, E23 and Atet have been studied in detail. Phylogenetic analyses identify the Drosophila gene dMRP/CG6214 as an orthologue to the human multidrug-resistance associated proteins MRP1, MRP2, MRP3 and MRP6. To study evolutionarily conserved roles of MRPs we have initiated a charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 75 publications
(103 reference statements)
1
37
0
1
Order By: Relevance
“…Demonstration of secretion of P-gp and MRP2 substrates by Drosophila tubules is of particular interest because of previous molecular genetic evidence for the presence of MDR and MRP genes in this species (Wu et al, 1991;Tarnay et al, 2004). Our results set the stage for further analysis of the effects of treatments, such as cadmium exposure and heat shock (Tapadia and Lakhotia, 2005), known to alter MRP or MDR gene expression on transport of P-gp and MRP2 substrates by isolated MTs and the possible role of such transport in insecticide resistance.…”
Section: Clsm Analysis Of Secreted Droplets Collected In Optically Flatmentioning
confidence: 99%
See 1 more Smart Citation
“…Demonstration of secretion of P-gp and MRP2 substrates by Drosophila tubules is of particular interest because of previous molecular genetic evidence for the presence of MDR and MRP genes in this species (Wu et al, 1991;Tarnay et al, 2004). Our results set the stage for further analysis of the effects of treatments, such as cadmium exposure and heat shock (Tapadia and Lakhotia, 2005), known to alter MRP or MDR gene expression on transport of P-gp and MRP2 substrates by isolated MTs and the possible role of such transport in insecticide resistance.…”
Section: Clsm Analysis Of Secreted Droplets Collected In Optically Flatmentioning
confidence: 99%
“…An ortholog of human MRP genes has been identified in Drosophila, although transport of MRP substrates by the MTs has not been tested. The Drosophila MRP (dMRP) gene contains 19 exons that are alternatively spliced, resulting in multiple isoforms (Tarnay et al, 2004).…”
mentioning
confidence: 99%
“…Until recently, expression of MRP orthologs in Drosophila was thought to occur uniformly throughout the body of the developing blastoderm and in the cephalic region of adult flies (Tarnay et al, 2004). However, subsequent microarray studies have shown that Malpighian tubules of D. melanogaster are particularly enriched for at least six ABC transporters, including members of the MRP family (Dow and Davies, 2006).…”
Section: Trnmrp Expression In the Malpighian Tubulementioning
confidence: 99%
“…Previous phylogenetic analyses have revealed that CG14079 may be an ortholog of MRP4/ABCC4 (8,40), which is thought to transport a diverse array of physiologically related substrates (8,36,41). Whereas the human MRP4/ABCC4 has been overexpressed in insect cells to study its role in cyclic nucleotide transport (33,44), the biological roles of Drosophila MRP4/ABCC4 homologs are yet to be determined.…”
Section: Overexpression Of Cg14709 Renders Adult Flies Anoxia Sensitivementioning
confidence: 99%